Analisis Faktor Risiko yang Berpengaruh Terhadap Kejadian Keracunan Pestisida Organofosfat pada Petani Penyemprot Hama Tanaman di Kecamatan Bulu, Kabupaten Temanggung, 2002. - Mualim, Khabib; Setiani, Onny; Hadisaputro, Suharyo (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2002)
ABSTRACT Background : Pesticides spraying which does not follow the regulation, will give many effect to human health. For example, the farmers will be Poisoning Pesticides Poisoning can be found by the examination of the blood cholinesterase activities. The factor that influence to the occurrence of pesticides poisoning are factors from the inside of the human body (internal) and the outside of the human body (external). Based on the result of examination of the farmer’s blood cholinesterase activities that had been carried on for four times, it showed that in year 1994, 58.4% from 65 person were Poisoned; in year 1997, 36.3% from 85 person were Poisoning in year 1999, 30.7% from 80 person were Poisoning, in year 2000, 65.3% from 80 persons were Poisoned. Methods : Research design used case-control study with 104 cases and 104 controls. Risk factors were the research area, age, nutritional status, anemia, pesticides processing, using of personal protective equipment, pesticides dose, the number of pesticides used, work duration, spraying duration, spraying frequency, spraying action in the same wind direction, and spraying time. The research was carried on in the sub district of Bulu, district of Temanggung, Central Java. Results : the number of Poisoning occurences in Pakurejo village are 30.3%, age group of 30 – 39 years are 30.8% and SD Graduation 59.1%. Risk factors that influence to the occurrence of pesticides Poisoning are nutritional status < 18.5 (OR = 6.78; 95% CI = 2.08 – 22.62); not properly pesticides dose (OR = 6.46; 95% Cl = 2.52-16.57); the number of pesticides types ³ 3 types (OR = 5.37; 95% Cl = 2.23-12.92); anemia (OR = 5.03; 95% Cl = 1.54-16.46); spraying frequency ³ 3 times (OR = 4.95; 95% Cl = 2.03-12.7); bad sprying times (OR = 3.94; 95% Cl = 1.70-9.17); age ³ 40 year (OR = 3.83; 95% Cl = 1.64-8.94); sprying action opposites the wind direction (OR = 3.43; 95% Cl = 1.37-8.62); and using of un complete personal protective equipment (OR = 2.83; 95% Cl = 1.19-19.68). Conclusion, nutritional status risk factor < 18.5 is the most influenced risk factor to the occurrence of organophosphate pseticides Poisoning at the sprayer farmers of plant pest. Key Word: Rick factors, Cholinesterease activities, Organophosphate Pesticides poisoning